(untitled) (Mustansiria Dental Journal, 2018)
Parathyroid hormones are playing an important role in maintaining calcium ion level in blood. The present study was design to evaluate the effect of parathyroid hormone is on bone in developing embryos. Ten albino pregnant rats were used in this study who 0.5 mg of parathyroid hormone as a tablets was given in drinking water from first day of gestation till delivery day (21). Treated embryos (No.50) of one day old were evaluated in comparison to control (No.50) radiographically and by measuring weight and size of the head. The results showed significant variation with low bone density in treated embryos. The study showed t